The Expected Skills from Learning English: Perspective from Culinary Students at SMKN 1 Sukasada - Siregar, Merry Amadea; Mahayanti, Ni Wayan Surya; Budiarta, Luh Gd Rahayu (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
The culinary industry demanded strong English communication skills, especially in speaking. This study aimed to identify the English language skills needed by tenth-grade culinary students at SMKN 1 Sukasada. A qualitative descriptive method was employed, involving 28 purposively selected students. Data were collected through closed and open questionnaires and analysed descriptively. The findings reveal that speaking skills are considered the most important aspect of English, yet students have limited exposure to English in their daily lives. Key challenges include a restricted vocabulary, difficulties with pronunciation, and low self-confidence. Therefore, the study recommends increasing English exposure outside the classroom, incorporating more speaking-focused activities, and providing targeted practice in vocabulary and pronunciation. A supportive learning environment is also essential to enhance students’ English abilities. Although the sample size is small, this study offers valuable insights for developing an English curriculum that addresses the specific communicative needs of vocational culinary students.